The Role of Pojok Budaya Community in Preserving Local Culture Through Cultural Tourism in Bantul - dian tarakanita (Jurnal Penelitian Humaniora, 2017)
The aims of the research are: (1) to know the role of the Pojok Budaya Community in preserving the local culture through cultural tourism, (2) to know the factors that make Pojok Budaya Community still exist in managing Kampung Dolanan. The descriptive qualitative research methods, and data collection techniques conducted through interviews, observation, questionnaires, and documentation. The results have obtained are: (1) The Pojok Budaya community has three roles, namely: a) cultural preservation: introducing the cultural meanings contained in every traditional game; b) child protection: creating a safe game for children; c) empowerment: empowering local communities to support cultural tourism; (2) Factors that make the Cultural Corner Community still exist in managing Kampung Dolanan are: a) the creative community itself, and b) availability of facilities and infrastructure.Keyword: Pojok Budaya, local cultural, cultural tourism